COMPARISON OF THE NUMBER OF MACROPHAGES IN THE RAT REVERSIBLE PULPITIS AFTER APPLICATION OF BIODENTIN AND SIWAK EXTRACT - Andina Rizkia Putri Kusuma; Rahmawati Sri Praptiningsih; Arlina Nurhapsari (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Oral disease still need special attention, especially in dentistry. Inflammation of the pulp is caused by the presence of irritants. One of the mechanical irritants is iatrogenic factors caused by operator error during preparation so that roof of pulp chamber is exposed. This condition is called reversible pulpitis/inflammation of the pulp. Cells that play a role during inflammation are macrophages which are the second defense cell after neutrophil apoptosis. A direct pulp capping procedure is indicated for this condition. The material commonly used is biodentin, but because the price tends to be expensive, alternative materials are needed. Siwak contains flavonoids which are known to play an important anti-inflammatory role in the healing of exposed pulp. The purpose of this study was to compare the number of macrophages in the dental pulp of rats with reversible pulpitis after administration of biodentin and siwak extract.Method: This research is a true experimental with a post test only group design, consisting of 2 treatment groups, namely the 75% siwak extract group and the biodentin group. The material is applied after the tooth has been prepared. The research sample used male wistar rats and sacrificed on the 3rd day. Samples were stained with Hematoxylin Eosin to see macrophage cells.Result: The data obtained were analyzed using the independent T-test. The test results showed a significant difference, with a value of p = 0.008 (p <0.05).Conclusion: The conclusion of this study that the siwak extract group showed a lower mean number of macrophage cells than the biodentin group.